The Association Between Cardiovascular Risk Factors and High Blood Pressure in Adolescents: A School-Based Study - Christofaro, Diego G. D. [UNESP]; Fernandes, Romulo A. [UNESP]; Oliveira, Arli R.; Freitas Junior, Ismael Forte [UNESP]; Barros, Mauro V. G.; Ritti-Dias, Raphael M. (Wiley-Blackwell, 2014)
Objective: Although previous studies have analyzed the association between cardiovascular risk factors and blood pressure in adolescents, few studies conducted in developing countries analyzed whether the aggregation of risk factors contributes to an increased risk of high blood pressure in adolescents. The objective of this study was to assess the association between cardiovascular risk factors (including general overweight, abdominal obesity, high consumption of foods rich in fats, and insufficient physical activity levels) and high blood pressure in adolescents.Methods: This study was carried out from 2007 to 2008 with 1021 adolescents (528 girls) from primary schools located in the city of Londrina- Brazil. Blood pressure was assessed using an oscillometric device. General overweight was obtained through body mass index, abdominal obesity was assessed using waist circumference, and the consumption of foods rich in fat and physical activity were assessed using a questionnaire. The sum of these risk factors was determined.Results: Adolescents with three or four aggregated risk factors were more likely to have higher values of systolic and diastolic blood pressure when compared with adolescents who did not have any cardiovascular risk factors (P = 0.001 for both). Logistic regression indicated that groups of adolescents with 2 (OR = 2.46 [1.11-5.42]; P = 0.026), 3 (OR = 4.97 [2.07-11.92]; P = 0.001) or 4 risk factors (OR = 6.79 [2.24-19.9]; P = 0.001) presented an increased likelihood of high blood pressure.Conclusions: The number of cardiovascular risk factors was found to be related to high blood pressure in adolescents. (C) 2014 Wiley Periodicals, Inc.